Collection understanding - Chang, Michelle; Leggett, John J.; Furuta, Richard; Kerne, Andruid; Williams, J. Patrick; Burns, Samuel A.; Bias, Randolph G. (Proceedings of the 4th ACM/IEEE-CS Joint Conference on Digital Libraries, 2004)
Collection understanding shifts the traditional focus of retrieval in large collections from locating specific artifacts to gaining a comprehensive view of the collection. Visualization tools are critical to the process of efficient collection understanding By presenting simple visual interfaces and intuitive methods of interacting with a collection, users come to understand the essence of the collection by focusing on the artifacts. This paper discusses a practical approach for enhancing collection understanding in image collections.